2013
DOI: 10.1186/1746-1596-8-177
|View full text |Cite
|
Sign up to set email alerts
|

USP9X expression correlates with tumor progression and poor prognosis in esophageal squamous cell carcinoma

Abstract: BackgroundUbiquitination is a reversible process of posttranslational protein modification through the action of the family of deubiquitylating enzymes which contain ubiquitin-specific protease 9x (USP9X). Recent evidence indicates that USP9X is involved in the progression of various human cancers. The aim was to detect the expression of USP9X in the progression from normal epithelium to invasive esophageal squamous cell cancer (ESCC) and evaluate the relevance of USP9X expression to the tumor progression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 32 publications
0
54
0
Order By: Relevance
“…Mounting evidence suggests that USP9X behaves principally as an oncogene in the context of many neoplasms. Studies have demonstrated that USP9X levels correlate with tumor cell growth and staging in a number of cancers including lung, 26 breast, 27 cervical, 22 chronic myelogenous leukemia, 24 colon, 28 esophageal carcinoma, 29 brain, 5 and to a limited extent, PDAC. 1 The data presented in this report supports the role of USP9X as a growth promoter in the context of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that USP9X behaves principally as an oncogene in the context of many neoplasms. Studies have demonstrated that USP9X levels correlate with tumor cell growth and staging in a number of cancers including lung, 26 breast, 27 cervical, 22 chronic myelogenous leukemia, 24 colon, 28 esophageal carcinoma, 29 brain, 5 and to a limited extent, PDAC. 1 The data presented in this report supports the role of USP9X as a growth promoter in the context of PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Both USP9x and UCH37 are over-expressed in many cancers(3033), so inhibition of these DUBs provides an attractive mechanism for the anticancer effects of ITCs (30,31,33). USP9x is known to protect the antiapoptotic protein Mcl-1 from ubiquitination and degradation(33).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, Xlinked deubiquitinase USP9X, the allele of USP9Y, has been reported to serve as a tumor suppressor gene in pancreatic ductal adenocarcinoma [34]. Moreover, recent studies have demonstrated a correlation between US9X expression and the formation, progression, and poor prognosis of ESCC (esophageal squamous cell carcinoma) [35]. In prostate cancer, it could stabilize ERG, which is a major driver of prostate cancer [36].…”
Section: Discussionmentioning
confidence: 98%